2023
DOI: 10.1038/s41598-023-46436-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface-exposed chaperonin 60 derived from Propionibacterium freudenreichii MJ2 inhibits adipogenesis by decreasing the expression of C/EBPα/PPARγ

Mirae An,
Young-Hee Lim

Abstract: Recent studies have shown that the health benefits of probiotics are not limited to those offered by living bacteria. It was reported that both live and killed cells of Propionibacterium freudenreichii MJ2 (MJ2) isolated from raw milk showed antiobesity activity in 3T3-L1 cells and high-fat diet-induced obese mice. This study was aimed at identifying the active component(s) responsible for the antiadipogenic activity of MJ2. Cell wall, surface protein, and cytoplasmic fractions of MJ2 were investigated for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A large number of different biological moonlighting functions have been ascribed to chaperonin 60 (Hsp60) proteins (46). Notably, a recent study revealed antiadipogenic activity of surface-exposed Hsp60 in P. freudenreichii strain MJ2 (47). For Helicobacter pylori Hsp60, extracellular properties include iron binding (48), an ability that could be beneficial in aerobic conditions, thus explaining differential surface abundance in response to atmospheric conditions for PFR .…”
Section: Resultsmentioning
confidence: 99%
“…A large number of different biological moonlighting functions have been ascribed to chaperonin 60 (Hsp60) proteins (46). Notably, a recent study revealed antiadipogenic activity of surface-exposed Hsp60 in P. freudenreichii strain MJ2 (47). For Helicobacter pylori Hsp60, extracellular properties include iron binding (48), an ability that could be beneficial in aerobic conditions, thus explaining differential surface abundance in response to atmospheric conditions for PFR .…”
Section: Resultsmentioning
confidence: 99%